2021
DOI: 10.3390/ijerph18115622
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Emotions and Stressors in Front-Line Healthcare Workers during the COVID-19 Outbreak in Mexico

Abstract: The aim of this study was to explore the knowledge, emotions and perceived stressors by healthcare workers who were in contact with infected patients during the COVID-19 outbreak. An online cross-sectional survey was applied. Data were collected from N = 263 healthcare workers in Tabasco State, Mexico. We developed and administered a questionnaire, which consisted of sociodemographic characteristics, plus four sections. The sections evaluated were (1) knowledge of COVID-19; (2) feelings/emotions during the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Telephone Interviews reported higher prevalences of these two disorders, reaching a third of the population [ 25 , 27 ]. Data from this study, combined with information obtained during the pandemic, point to the importance of attending to an important problem affecting an important part of the population [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telephone Interviews reported higher prevalences of these two disorders, reaching a third of the population [ 25 , 27 ]. Data from this study, combined with information obtained during the pandemic, point to the importance of attending to an important problem affecting an important part of the population [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in stress-induced regulation via any genetic factor could have important influences on SB. Some stress pathways genes that have been studied in SB include NR3C1, [19,20]; FKBP5 [21,22]; CRHR1 [23,24]; and SKA2 gene [25,26]. Candidate gene studies have shown differentially expressed mRNA patterns and single-nucleotide polymorphisms (SNPs) in Caucasian and African American populations associated with SB [27,28].…”
Section: Figurementioning
confidence: 99%
“…Eighteen studies [19,21,22,28,[31][32][33][34][35][36][37][38][39][40][41][42][43][44] analyzed the association between FKBP5 SNPs and SB phenotypes comprising 4239 cases and 9646 controls. The first study conducted in 2007 by Papiol et al [31] highlighted a significant association between the rs1360780 SNP and SA.…”
Section: Fkbp5 Genementioning
confidence: 99%
“…In developed countries the data about the impact on mental health workers is abundant; however, in low-income and middle-income countries, such as Mexico, the data is scarce. Regarding the data for Mexico, the most common psychological consequences reported are insomnia, depression, and post-traumatic stress disorder, with physicians and paramedics the most affected [12,13]. In a study that evaluated the psychological impact on 462 Mexican nurses, the researchers identified that 46.72% of them had traumatic stress responses from moderate to severe, and that 42.40% of participants exhibited a high level of emotional exhaustion [14].…”
Section: Introductionmentioning
confidence: 99%